Improvising Joy (January 2020) - Richardson, Justine (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2025)
Justine Richardson shares a reflection on Ajay Heble's joy, which she witnessed as former Project Manager of the International Institute for Critical Studies in Improvisation (IICSI).